2011
DOI: 10.4014/jmb.1007.07051
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Multiplex PCR Assay for the Simultaneous Detection of the Brucella Genus, B. abortus, B. melitensis, and B. suis

Abstract: The routine identification and differentiation of Brucella species is a time-consuming and labor-intensive process, which frequently places personnel at risk of laboratoryacquired infection. Here, we describe the development of a rapid multiplex PCR assay for the confirmation of presumptive Brucella isolates. The assay was able to identify and differentiate major human pathogens, namely B. abortus, B. melitensis, and B. suis, in a single test of less than an hour and a half.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
0
19
1
1
Order By: Relevance
“…Also, finding denaturation temperature, denaturation duration, and the annealing temperature are important subjects which are valuable and time consuming and require expert personnel. In contrast with other studies (20, 21), our study showed difference in sensitivity because of protocol conditions such as concentrations of primers, dNTPs, MgCl 2 , and Taq polymers. In the study by Da Costa et al , the specificity of primers on the 98 non- Brucella bacteria, mentioned that all organisms were negative for amplification of the BCSP31 gene (22).…”
Section: Discussioncontrasting
confidence: 99%
“…Also, finding denaturation temperature, denaturation duration, and the annealing temperature are important subjects which are valuable and time consuming and require expert personnel. In contrast with other studies (20, 21), our study showed difference in sensitivity because of protocol conditions such as concentrations of primers, dNTPs, MgCl 2 , and Taq polymers. In the study by Da Costa et al , the specificity of primers on the 98 non- Brucella bacteria, mentioned that all organisms were negative for amplification of the BCSP31 gene (22).…”
Section: Discussioncontrasting
confidence: 99%
“…Rapid latex agglutination tests can also be useful in areas with limited laboratory capacity, and one study using culture-confirmed cases and negative controls demonstrated a sensitivity of 89% and a specificity of 98% [89]. PCR was effectively employed to rapidly detect Brucella DNA in the blood of six suspected cases which all subsequently met confirmed case definitions [90], and multiplex assays can expedite the confirmation and speciation of Brucella isolated by culture [91,92]. A real-time PCR assay that rapidly and accurately distinguishes Brucella from M. tuberculosis in body fluid and tissue specimens holds promise for clinical use [93].…”
Section: Clinical Diagnosis and Diagnostic Advancesmentioning
confidence: 99%
“…Brucella melitensis, C. sakazakii and L. monocytogenes have been identified by conventional methods and real-time PCR (RTi-PCR) methods (Germini et al 2009;Kumar et al 2011;Jun-Ichi et al 2012). Conventional methods do not provide the desired accuracy, precision and speed, and sufficient information for quantitative detection of microorganisms compared with RTi-PCR technology.…”
Section: Introductionmentioning
confidence: 99%